Pengaturan Pemilihan Kepala Daerah dalam Sistem Ketatanegaraan Indonesia Setelah Perubahan - AR, Hamdani (Jurnal Jatiswara, 2017)
The Implementation of elections in accordance with the provisions of the Regional Head UUDN RI 1945 after a change of the Article 18 paragraph 4 can be interpreted that the implementation of the Regional Chief Elections system can be implemented indirectly (through election by parliament) and direct local elections (by the people directly), the whole process is carried out in a democratic manner. Commentaries can cause legal problems (conflict of norm, disconsistency of norm, and vague of norm) so that in practice cause multiinterpretasi Indonesia in the state system, which can lead to injustice, undemocratic, there is no rule of law and contrary to human rights particularly in the intellectual, empowerment and restrictions of expression orally or in writing. As for direct elections by the people as is done now are those many negative impacts on the development of people's lives so that the purpose and benefits of regional head elections is not achieved directly in line with expectations (hopeless). Therefore the issues raised in this writing is How to Perspective setting in the future local elections?. Based on the research, the authors ultimately conclude in answer to the problems is that; the local elections Setting Perspective for the Future is done by direct democratic election in accordance with Article 18 paragraph 4 UUDN RI 1945 which followed the democratis indirect approaches, namely democratic elections by the people's representatives are elected by the Council of the Regional Perwaikilan (Parliament), because of various considerations such as: efficiency budgets, Avoiding conflict, Minimizing the anarchic actions, prevent the use of the bureaucracy or the direction of civil servants (PNS), Avoiding political money. Therefore it is expected that in the future will be done democratically through the parliament elections, in order to provide more safety and comfort of the community.